Dataset on teacher well-being and student–teacher relationships in Indonesian schoolsOSF - Airin Yustikarini Saleh; Farida Kurniawati; Rose Mini Agoes Salim (Data in Brief)
This dataset consists of responses from 1341 school teachers in Indonesia, collected through self-report questionnaires designed to measure teacher-student relationships, and teacher subjective well-being. The data were gathered using non-probability convenience sampling in adherence to COVID-19 restrictions and were analyzed using correlation analyses and tests of differences with IBM SPSS Statistics version 25. The dataset offers a comprehensive, descriptive view of teachers' self-reported levels of perceptions of their relationships with students and overall subjective well-being. It also includes demographic variables such as age, gender, and teaching level, which enable a more nuanced analysis of how these factors may interact with teacher well-being. This makes the dataset particularly valuable for researchers, educational psychologists, and policymakers interested in understanding the factors influencing teacher well-being and educational outcomes. The data can be used for longitudinal studies, meta-analyses, and comparative research across different demographic subgroups. Additionally, the insights derived from this dataset can support the evaluation of educational policies and the development of evidence-based strategies aimed at enhancing teacher support, improving retention, and fostering a more supportive educational environment.